When the voice becomes and the dummy speak - Santos, Daiana Nascimento dos (Revista de Letras, 2017)
This paper presentes an analysis of the novel A gloriosa familia (1997) Pepetela Angolan writer is performed. To investigate the literary representation of the history of Angola, approaches Ana Mafalda Leite (2003) on post colonial theories are used; the notion of intertextuality, Kristeva (1981) and Ainsa approaches (1996) on the historiographical narrative theme. Moreover, consideringo ther specific features of the novel, references to studies on memory and oral tradition are included to facilitate understanding of the way this narrative reconfigures the issue in question.